PENGARUH STIMULASI PERMAINAN ULAR TANGGA TENTANG GINGIVITIS TERHADAP PENGETAHUAN ANAK USIA 8-11 TAHUN Studi terhadapSiswa SD Negeri Kuningan 04, Kecamatan Semarang Utara - Syarifah Nur Laili Siyam; Arlina Nurhapsari; Benni Benyamin (ODONTO : Dental Journal, 2015)
Background: Health education was an attempt to increase the knowledge of children to health problems. The provision of health education can be done through stimulation using Educational Educative Equipment (APE) form snakes and ladders game . One of the health problems that was unfamiliar to the child that is gingivitis. Purpose: This study was conducted to determine the effect of stimulation of gingivitis snakes and ladders game against the knowledge of children ages 8-11 years. Method: This research method using descriptive analytic with pre and post test design. Samples were collected using simple random sampling method comprising 102 respondents based on inclusion criteria of the SD N Kuningan 04. The independent variable is the stimulation of snakes and ladders game. The dependent variable is the child's knowledge about gingivitis. Data were collected using a questionnaire and analyzed the Wilcoxon Signed Rank test. Result: Based on the Wilcoxon Signed Rank test showed significance value 0.00 (p <0.05), so it can be concluded that health education using stimulation of snakes and ladders game has the effect to increase the knowledge of gingivitis in children. Conclusion: From these results it can be concluded that education using the stimulation of snakes and ladders game effect to increase children's knowledge about gingivitis.